2019
DOI: 10.1590/1984-0462/;2019;37;3;00014
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of the Father in the Care of the Hospitalized Preterm Infant: Perception of the Multiprofessional Team

Abstract: Objective: To understand the perception of the multiprofessional health care team regarding the inclusion of fathers in the care of preterm infants who are in Intensive Care Units (ICUs).Methods: This is a descriptive study with a qualitative approach, using a semi-structured interview with 12 health care professionals of a neonatal ICU, from February to July 2017. The data were analyzed according to the Discourse of the Collective Subject.Results: Seven main ideas (MI) emerged from the text analysis, which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
2
7
0
4
Order By: Relevance
“…Work and other responsibilities have been reported in the current study as impeding fathers' involvement in the care of hospitalized preterm newborns. This is consistent with ndings from other studies [13,[44][45][46][47], which reported that multiple responsibilities prevented the fathers from being engaged in caregiving activities. It is worth noting that at the time of the study, the Malawi labour laws were not allowing for paternal leave for those formally employed, and also the majority of the participants were not in formal employment which meant they still needed to work to earn something for the families.…”
Section: Discussionsupporting
confidence: 92%
“…Work and other responsibilities have been reported in the current study as impeding fathers' involvement in the care of hospitalized preterm newborns. This is consistent with ndings from other studies [13,[44][45][46][47], which reported that multiple responsibilities prevented the fathers from being engaged in caregiving activities. It is worth noting that at the time of the study, the Malawi labour laws were not allowing for paternal leave for those formally employed, and also the majority of the participants were not in formal employment which meant they still needed to work to earn something for the families.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies assessed paternal bonding qualitatively instead of using a quantitative measurement tool. Of these, ten studies used interviews [ 23 , 26 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ], two used group discussion methods [ 71 , 72 ], and three observed fathers’ interactions or reactions [ 29 , 31 , 73 ]. A study based in Japan measured paternal bonding via a mixed-methods approach.…”
Section: Resultsmentioning
confidence: 99%
“…Furukawa et al [ 25 ] reported that communication and early experience/involvement after delivery with their babies were crucial factors for improving and promoting paternal–infant bonding. In addition, taking care of their babies directly, such as by massaging and feeding, and being closer to their babies through affectionate actions such as seeing their face, talking to them more with a monotonous tone, and holding them for long durations were related to the development of a bond [ 29 , 58 , 70 , 74 , 76 ]. For example, bottle feeding was associated with father–infant bonding.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, they understand that this environment may be able to minimize the impact that the child suffers when leaving the womb beforehand and, thus, increase his/her chances of survival. 5,6 The father's participation during his child's hospitalization is essential, especially because he is considered a support figure for the mother and the newborn. For some fathers, parenthood emerges after the beginning of contact and interaction with the baby, therefore, their entry into the hospitalization units must occur without the imposition of pre-established schedules.…”
Section: Introductionmentioning
confidence: 99%